Nuevos rumbos del comparatismo: literatura comparada y literatura–mundo (El Hilo de la Fabula, 2019)
Since its inception and consolidation as an academic discipline in the second half of the nineteenth century, the field of comparative literature has undergone significant transformations. Far from ascribing to binary studies around the work of authors, literary masterpieces or approaches or the Western canon, this discipline has remained open to all kinds of literary and cultural manifestations and receptive of other knowledge areas, thus becoming a true dialogue amongst cultures. Among the changes that the scope of comparative literature has experienced, we hereby highlight the «circulation» of a given literary masterpiece, often characterized by a good reception on the part of translation studies and by the emphasis placed on its reception context; which in tandem has given birth to a research arena within this field that is known as «world literature». In this text, we will attempt toreflect upon the aforementioned transformations regarding the spectrum of comparative literature and try to demonstrate that far from being forgotten, the discipline has been completely revitalized.
Keywords: Comparative literature; world literature; new paths